Electrospun ZIF-derived cavity porous carbon nanofibers as a freestanding cathode for lithium–oxygen batteries with ultralow overpotential. Issue 39 (4th October 2021) - Peng, Lichong; Zhang, Xiuling; Sun, Yaxin; Li, Congju
Abstract : We have developed a feasible approach to establish a freestanding air-cathode based on Co–N x species trapped in hierarchical porous carbon nanofibers with reduced charge-discharge polarization (0.36 V) and high initial specific capacity (12.12 mAh cm −2 ) for Li–O2 batteries. Abstract : Construction of an efficient electrocatalyst for the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) with low overpotential and cycling stability for lithium–oxygen batteries still remains a puzzling challenge. Herein, we propose a scalable approach to integrate ZIF derivatives into cavity porous carbon nanofibers (CPCNFs) via an electrospinning technique and thermal treatment (Zn/CoNC@CPCNFs). The ultralong interconnected nanofiber matrix is beneficial, and the developed Zn/CoNC@CPCNFs catalyst with excellent flexibility can be utilized as a free-standing electrode based on an air-cathode. Moreover, this confinement strategy ensures the dispersion of Co-based species and abundant porosity structure, which contributes to the transport and adsorption of oxygen and exposes more Co–N coordination catalytic centers, as a result of a drastically ultralow voltage gap. Consequently, a cell based on a Zn/CoNC@CPCNF electrode presents remarkably decreased charge–discharge polarization (0.36 V), a high initial discharge capacity with an ultra-low overpotential of 0.59 V, and long-term cyclability with a cut-off capacity of 0.2 mA h cm −2 at 0.02 mA cm −2 . We hope that our protocol will offer instruction for the design and application of oxygen electrocatalysts for energy conversion and storage.